ANALISIS PROSES PEMBELIAN DAN PENJUALAN BERAS OLEH PENGGILINGAN PADI DI INDONESIA - , Agus Sakbani, SP. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Rice mills is also determining the amount of available rice, quality of rice that consumed, the price level, farmers' income, level of consumer prices and also determine the availability of jobs in rural areas. But in practice in Indonesia found many differences in the process of buying and selling rice paddy milling. The purpose of this study was to analyze the process of riceâs buying and selling by rice mills in Indonesia and to analyze the presence or absence of differences in the process of buying and selling rice by rice mills among the areas in Indonesia. The basic method used in this research is descriptive method of analysis. Sampling was performed quota sampling rice mill. Population in this study were rice mills in Indonesia, while the number of samples taken is limited to 100 samples. Sampling was conducted in rice mills convenience sampling. Data analysis technique used is the frequency analysis and statistical tests ANOVA test (F test). The results showed that the process of purchasing paddy generally indicates that the rice mills buy unhulled paddy from farmers (36%). Most of the paddy rice mill buy unhulled paddy in cash as many as 77 respondents out of 100 respondents (77%). Most of the rice mill rice mill service in cooperation with the Bulog (51.16%). The process of selling rice in Indonesia generally indicates that rice mills providing services and sell rice without using its own brand (57.89%). Most respondents sell rice to the Rice Seller (55%). Most of the rice mill in Indonesia sell its rice in the district itself as much as 60%. Based on the analysis also can be seen that the process of buying and selling of paddy by different rice mills give different results for each area. Both in terms of Purchasing Sources Rice, How To Buy Rice, Rice Milling Sales Product Service, Sales Objectives of Rice, Rice Sales Region